The risk of recurrence in surgically treated head and neck squamous cell carcinomas: a conditional probability approach. (3rd July 2021) - Borsetto, Daniele; Sethi, Mantegh; Polesel, Jerry; Tomasoni, Michele; Deganello, Alberto; Nicolai, Piero; Bossi, Paolo; Fabbris, Cristoforo; Molteni, Gabriele; Marchioni, Daniele; Tofanelli, Margherita; Cragnolini, Fiordaliso; et al.
Abstract: Background: Over 50% of patients with head-and-neck squamous cell carcinoma (HNSCC) experience locoregional recurrence, which is associated with poor outcome. In the course of follow-up for patients surviving primary surgery for HNSCC, one might ask: What is the probability of recurrence in one year considering that the cancer has not yet recurred to date? Materials and methods: To answer this question, 979 patients surgically treated for HNSCC (i.e. cancer of the oral cavity, oropharynx, hypopharynx or larynx) between March 2004 and June 2018 were enrolled in a multicenter retrospective cohort study, followed up for death and recurrence over a 5 year period. The conditional probability of recurrence in 12 months – i.e. the probability of recurrence in the next 12 months given that, to date, the patient has not recurred – was derived from the cumulative incidence function (Aalen-Johansen method). Results: Overall, the probability of recurrence was the highest during the first (17.3%) and the second years (9.6%) after surgery, declining thereafter to less than 5.0% a year thereafter. The probability of recurrence was significantly higher for stage III–IV HNSCCs than for stage I–II HNSCCs in the first year after surgery (20.4% versus 10.0%; p < 0.01), but not thereafter. This difference was most pronounced for oral cavity cancers. No significant differences were observed across different tumor sites. Conclusion: This dynamic evaluation of recurrence risk in patients surgically treated for HNSCC provides helpful and clinically meaningful information, which can be useful to patients in planning their future life, and to clinicians in tailoring post-treatment surveillance according to a more personalized risk stratification.